Audit committee characteristics and internal audit budget: Malaysian evidence - Almagdoub, Almahdi Ali Mohamed Saleh (2016)
An audit committee is viewed as an essential self-regulatory internal governance instrument that is expected to provide an overseeing role over the entire process of financial reporting. An internal audit is also one of the corporate governance cornerstone that is essential for the effective monitoring of the operating performance of internal control. To ensure its effectiveness, the audit committee monitors the resources available to the internal audit, and internal control functions should be directly reported to the audit committee. This study is set out to explore the effect of audit committee characteristics (i.e independence, expertise, meeting and tenure) on internal audit budget in Malaysia, where governance mechanisms are suboptimal. The study also opens the door to an unanswered question, that is, whether an audit committee index is related to internal audit budget. Data of 96 companies listed on Bursa Malaysia for a three-year period, 2012-2014, was utilized to achieve this end. The regression result shows that there is audit committee meeting and index are significantly and positively associated with internal audit budget. They also indicate that audit committee tenure has a significant and negative impact on internal audit budget. The theoretical, practical, academic and regulatory implications of these findings were discussed in details. On one extreme, the findings of the study supports the recent policy initiatives in relation to audit committee and internal audit. On the other extreme, the result serves as a wake-up call to policy makers in requiring more committed, competent and skilled members on the audit committee.